Manufacturing of oral solid dosage forms using 3D inkjet printing - Kyobula, Mary (2017)
Ink-jet printing is a precise and versatile technique that accurately deposits small volumes of solutions (pico litres) in specific locations. Recently inkjet printing has attracted increasing attention in the pharmaceutical industry because of its ability to deliver low adjustable doses, variable drug release profiles and drug combinations suitable for the paradigm of personalised medicines. The significant growth in the aging population and the rise in the number of patients suffering from multiple chronic diseases are the key drivers. The current traditional tablet compression methods are largely limited in terms of flexibility and complexity of dosage form. There is a need for new innovative technologies that can produce bespoke medicines in a relatively cheap and efficient manner at the point of care. 3D inkjet printing (3DIJP) provides a platform with the potential to address the above need. This thesis investigates the capability of 3DIJP as a tool for manufacturing solid dosage forms. In chapter 3, a piezoelectric drop on demand printer was used. The chapter focuses on two solvent based inkjet printing methods. In the first solvent based method, excipients including hydroxypropyl methylcellulose (HPMC), poly (vinyl pyrrolidone) (PVP) and Eudragit RL were investigated for printability. PVP (K10) which showed the best printability behaviour was loaded with digoxin or carbamazepine (CBZ) and printed to obtain films. In the second solvent based method, a solution containing CBZ dissolved in a mixture of of polyethylene glycol diacrylate (PEGDA) and with poly(caprolactone dimethyl acrylate) (PCLDMA) was printed and polymerised in situ using ultraviolet light to form films. The printed drug loaded films were investigated using time of flight secondary ion mass spectroscopy (ToF SIMS), atomic force microscopy (AFM), scanning electron microscopy (SEM) and differential scanning microscopy (DSC). PVP formulations were homogeneous, with no evidence of crystallisation PEGDA/PCLDA/CBZAFM images showed a clear phase separation at the micron scale and no drug was detected at the surface. In this chapter, the production of adjustable doses was also evaluatedusing UV-VIS spectrophotometry. In chapters 4 and 5, a solvent-free hot-melt 3D inkjet printing method suitable for manufacturing solid dosage forms was developed. Excipients including beeswax, carnuba wax, gelucire 44/14 and trimyristin were examined for printability. Beeswax a naturally derived and FDA approved material showed the best printability behaviour and was selected as the drug carrier. Traditional circular shaped tablets and cylindrical implants loaded with 5% w/w fenofibrate were successfully fabricated. The printed tablets and implants were well-defined, smooth surfaced and with no apparent defects. The architecture of the tablets was investigated using 3D micro X-ray computed tomography (μCT), revealing well defined and ordered honeycomb channels in the interior of the tablets. The distribution of the drug was evaluated at the macro scale level using DSC and at the micro scale level using ToF - SIMS and Raman spectroscopy. The drug was homogenously distributed within the drug carrier (beeswax matrix ) at the microscale level. At the micron scale level, the drug was heterogeneously distributed. ToF - SIMS studies also revealed that the drug was depleted from the upper most top surfaces. Production of solid dosage forms with intricate and adaptable geometries was demonstrated by printing honeycomb architecture tablets with predetermined variable cell diameters. The diamater of the honeycomb cells was varied, in order to achieve controlled variable drug release profiles. The ablity to control drug release was only applicable above an established critical cell diameter of 0.5 mm. An analytical model describing Fickian diffusion from a slab geometry was developed to allow for the prediction of drug release from the honeycomb tablets. The predicted drug release profiles varied slightly from the experimental data, but the trends for the two data set were identical. For both data sets the rate of drug release increased with increase in the surface area to volume ratio. The findings and the developments demonstrated in this thesis provide an insight into the potential application of 3DIJP as a tool for manufacturing solid dosage forms with bespoke properties for controlled drug release but also highlights some limitations.